The Thought of Yaroslav Stetsko Compared with the Views of Vojtech Tuka to 1941: On Two Variants of Integral Nationalism in Central and Eastern Europe - Wojnar, Marek (Kwartalnik Historyczny, 2024)
The inter-war period and the first years of the Second World War were a period when integral nationalism and Fascism were triumphant throughout Europe. The Ukrainian and Slovak national movements were no exception in this regard. These ideologies developed primarily within the framework of the Organization of Ukrainian Nationalists and the Hlinka’s Slovak People’s Party, respectively. This article compares the thought of representatives of the more radical factions within these two organizations: Yaroslav Stetsko and Vojtech Tuka.